2023
DOI: 10.3390/microorganisms11092159
|View full text |Cite
|
Sign up to set email alerts
|

First Detection and Molecular Characterization of Pseudomonas aeruginosa blaNDM-1 ST308 in Greece

Katerina Tsilipounidaki,
Christos-George Gkountinoudis,
Zoi Florou
et al.

Abstract: The objective of the present study is to report the detection and the molecular characterization of nine blaNDM-1-positive Pseudomonas aeruginosa isolates, all of which belonged to the epidemic high-risk international clone ST308, and all were isolated from patients in a tertiary care hospital in Central Greece from May to July 2023.The isolates were characterized by whole genome sequencing to obtain multi-locus sequencing typing (MLST) and identify the blaNDM1-environment and resistome and virulence genes con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2025
2025

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 30 publications
0
2
0
Order By: Relevance
“…Studies have shown that 35% of P. aeruginosa isolates are carbapenem-resistant, with most of them expressing numerous resistance mechanisms. As far as carbapenemases are concerned, most carbapenemase-producing P. aeruginosa strains produce MBLs [ 125 ]. Based on these epidemiological data, diagnostic and therapeutic algorithms are proposed in Figure 2 and Figure 3 .…”
Section: Carbapenemase Detection—rational Testing and Treatment Optio...mentioning
confidence: 99%
“…Studies have shown that 35% of P. aeruginosa isolates are carbapenem-resistant, with most of them expressing numerous resistance mechanisms. As far as carbapenemases are concerned, most carbapenemase-producing P. aeruginosa strains produce MBLs [ 125 ]. Based on these epidemiological data, diagnostic and therapeutic algorithms are proposed in Figure 2 and Figure 3 .…”
Section: Carbapenemase Detection—rational Testing and Treatment Optio...mentioning
confidence: 99%
“…In Central Greece, according to recent epidemiological data, 70% of CRPA strains carry either the bla VIM or the bla NDM gene; whereas, the remaining 30% seem to have a different mechanism of resistance [13]. The objective of the present study was the investigation of the mechanism of resistance of carbapenemase-negative carbapenem-resistant P. aeruginosa strains, focusing on the characterization of their β-lactamases combined with the changes in proteins encoded by the oprD, mexT, mexR, nalC, and nalD genes.…”
Section: Introductionmentioning
confidence: 99%